Design and evaluation of experiences based on social robots - Mendoza Cruz, Liany; Cerezo, Eva; Baldassarri, Sandra (Jornada de Jóvenes Investigadores del I3A, 2025)
The main objective of the work is to design and evaluate experiences based on social robots, focusing on interaction and intergenerational aspects, to improve the cognitive, physical and emotional well-being of people, and to foster the acceptance of these technologies in a more inclusive society.